Pelatihan Adversity Quotient untuk Optimalisasi Pribadi yang Tangguh pada Pendidik PAUD: indonesia - Nawangsih, Sri Kandariyah; Wangge, Maria Yuliana Wangge; Katkar, Kimmy Katkar; Pribadi, Agung Santoso (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Early childhood education educators have a role in shaping children's character from an early age. Early childhood is in a golden age where the role of parents, teachers, and the surrounding environment is needed to support the growth and development of children. In reality, in the process of educating children at school, children are not ready to be separated from their parents, children become tantrums and are not cooperative in learning, even differences in how to educate children between parents and educators cause their own problems. Differences of opinion between educators, as well as the increasing administrative burden of educators, cause educators to experience various difficulties that affect their duties, roles, and responsibilities as educators. This community service activity aims to provide adversity quotient training to early childhood education educators with the hope that the results of the training can help educators be more resilient in dealing with various problems faced. The training method is carried out by giving lectures, ice breaking, and providing pretests and posttests to training participants. The results of the analysis of adversity quotient training activities through the Wilcoxon T-test showed that 50 data (N = 50) showed that the post-test value was greater than the pre-test value, with a mean rank of 25.50 and a sum of ranks of 1275.00 with a Z value of -6.187 (p 0.000). Based on these results, it can be concluded that the training that was carried out effectively contributed to increasing participant understanding, considering that the post-test score was higher than the pre-test. Through this activity, participants have a better understanding that every problem has a solution and therefore the ability to survive in difficult situations and remain enthusiastic about finding solutions through various means is needed, even making difficulties an opportunity to overcome problems as well as possible.